(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Efavirenz, a non-nucleotide reverse transcriptase inhibitor is an important drug for treating patients with Human Immunodeficiency Virus infections. It belongs to BCS class II have low solubility and poor intrinsic dissolution rate. It is highly basic (pKa 10.2) which makes it suitable candidate for floating dosage form for continuous delivery in stomach.The study was aimed to improve the solubility by solid dispersion technique.Saturation solubility study and drug content were evaluated for solid dispersion preparation. Saturation solubility shows 8 fold increases in 0.1 N HCL compared to plain drug and drug content was found to be between 95%-102%. Further effervescent floating gastroretentive drug delivery system was prepared by 32 full factorial design with independent variables i.e., concentration of HPMC K100 as matrix forming agent and citric acid as gas generating agent. Lag time, floating time, percent drug release were studied as responses. The optimized batch exhibited floating lag time of 40 sec and the in vitro release studies showed 89.5% drug release in 9 h and tablet remained floating for greater than 8 h. The study thus demonstrated that solubility is increased by solid dispersion technique and floating delivery systems may increase solubility and bioavailability of Efavirenz.